2014
DOI: 10.15275/rusomj.2014.0305
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of preferred learning styles in medical education using VARK modal

Abstract: Learning styles is a term used to refer to the methods of gathering, processing, interpreting, organizing and thinking about information. Students have different learning styles, which is the reason for the diversity seen in classrooms in regards to how students acquire information. Claxton and Murrell had divided the learning styles into the following four categories: personality models, information-processing models, social-interaction models, and instructional preferences models. VARK (an acronym for Visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…18 These results are supported by a literature which suggests that preferred mode of learning is variable in different parts of the world. 19 However, it is worth discussing the low preference of auditory mode in this study. A traditional lecture is a typical example of auditory mode of learning which supports passive learning and encourages rote memorization.…”
Section: Discussionmentioning
confidence: 86%
“…18 These results are supported by a literature which suggests that preferred mode of learning is variable in different parts of the world. 19 However, it is worth discussing the low preference of auditory mode in this study. A traditional lecture is a typical example of auditory mode of learning which supports passive learning and encourages rote memorization.…”
Section: Discussionmentioning
confidence: 86%
“…(Kumar et al, 2012:9) Although in the current day, the investigation of gender might seem to be an overemphasis on the biological differences and their possible impact on ones" behavior and habits, these biological differences may have led to different social roles that consequently led to the creation of "two separate subcultures". (Almazroui, 2010:13) According to research, there are a number of differences between the two genders when it comes to learning styles (Oxford 1995, Cheng et al 2010, Khanal et al 2014.Male students are found to be "…more field-independent, implemented tactile learning, had superiority in spatial learning tasks, liked to read individually or in pairs… usually moved during the "reading time" and acquired or learned information more easily through left-hemispheric, analytic modes, generally had better achievement in logic and mathematical content" (Hou, 2015: 3). On the other hand, the "female students preferred visual styles; auditory and kinaesthetic styles, worked in groups , acquired language or learned through an integration of left-and-right-hemispheric modes, and (are) good at linguistic tasks."…”
Section: Gender As a Possible Influential Variablementioning
confidence: 99%
“…On the other hand, the "female students preferred visual styles; auditory and kinaesthetic styles, worked in groups , acquired language or learned through an integration of left-and-right-hemispheric modes, and (are) good at linguistic tasks." (Hou 2015:3)According to Khanal et al(2014), males preferred to use rational and logical evaluation, and they also seemed to be achievement oriented whereas females use "elaborative processing" and establish personal connections with the subject matter and are "socially and performance oriented". (5) When both genders were tested using VARK, the results indicated that the female subjects were multi modal, having a diverse combinations of multimodal leanings styles.…”
Section: Gender As a Possible Influential Variablementioning
confidence: 99%
See 1 more Smart Citation
“…VARK (an acronym for visual, aural, read/write, and kinesthetic, different way of learning styles) is a learning inventory belongs to the "instructional preference" modal which differentiates students by the way in which they best acquire information. [3] The VARK inventory is a tool which is easy to use and can give students information on how to maximize their learning. It is designed to be a starting place for a conversation among teachers and learners which is a useful step toward understanding, and hence, improving learning.…”
Section: Introductionmentioning
confidence: 99%